(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Employability skills are the prime topic of discussion among the academicians, corporate and training providers in this domain. Many engineering institutes are channelizing their focus in enhancing the employability skills of their students to raise the quality of placements in their campus. Beside, employability skills can also be considered as an alternate approach to resolve the unemployment issues in the emerging economies like India. The present study analyses the association of employability skills of engineering students on their perceived employability. Built on the employability skills framework of Jackson (2012) and perceived employability scale proposed by Roothwell et al.(2008), the study empirically validate these two constructs on a sample of engineering students from India. Confirmatory factor analysis validated the applicability of the constructs. The associations between employability skills and perceived employability have been found positive. Further, the role of entrepreneurial initiative and problem solving were assessed as a mediator between employability skills and perceived employability using structure equation modeling. The results of the study matches with the findings of previous studies and also look at the dimension of entrepreneurial initiative and problem solving as mediators in the relation between employability skills and perceived employability of the engineering students. The study confirm the association of previously identified factors of employability skills with that of perceived employability of fresh graduates and highlights the importance of entrepreneurial initiative and problem solving as a mediator in the existing model. Engineering institutes can channelize their training efforts to improve the problem solving skills and entrepreneurial orientation of the students that inculcate the intrapreneur trait in their personality. This will indirectly improve their employability skills. Students can also get benefits by acquiring entrepreneurial initiative and problem solving skills to strengthen their employability skills set.